Penggunaan Media Flash Card dalam Pengembangan Kemampuan Bahasa Anak Usia Dini - Riadoh Riadoh; Larasati Larasati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Language serves as a medium for interpersonal communication. The acquisition of language in children commences during infancy and progresses through exposure and linguistic maturation. The enhancement of linguistic abilities in early childhood is geared towards acquainting and enhancing their linguistic repertoire, enabling effective verbal interaction with their surroundings. The realm of language proficiency encompasses four key components: listening, speaking, reading, and writing. A method employed to foster linguistic proficiency involves the utilization of flashcards. The approach employed in this study involves a review of existing literature. The findings revealed that the utilization of flashcard materials has the potential to enhance linguistic abilities among young children by incorporating visual elements such as images, alphabets, symbols, and colors. This, in turn, captures the attention of children, facilitates easier retention of new words, enables recognition of letter shapes and sounds, enhances listening skills, promotes critical thinking, and encourages verbal expression, as evidenced by their communication proficiency.